Articulatory coordination distinguishes complex segments from segment sequences. Issue 3 (August 2021) - Shaw, Jason A.; Oh, Sejin; Durvasula, Karthik; Kochetov, Alexei
Abstract : Phonological patterning motivates a distinction between complex segments and segment sequences, although it has also been suggested that there might be reliable phonetic differences. We develop the hypothesis that, in addition to their distinct phonological patterning, complex segments differ from segment sequences in how constituent articulatory gestures are coordinated in time. Through computational simulation, we illustrate predictions that follow from hypothesised coordination differences, showing as well how coordination is conceptually independent of temporal duration. We test predictions with kinematic data collected using electromagnetic articulography. Electromagnetic articulography data comparing labial-palatal gestures in Russian, which we argue on the basis of phonological facts to constitute complex segments, and similar labial-palatal gestures in English, which we argue constitute segment sequences, show distinct patterns of coordination, providing robust support for our main hypothesis. At least in this case, gestural coordination conditions patterns of kinematic variation that clearly distinguish complex segments from segment sequences.